2021
DOI: 10.1186/s12909-020-02465-y
|View full text |Cite
|
Sign up to set email alerts
|

Reflective practice and transcultural psychiatry peer e-learning between Somaliland and the UK: a qualitative evaluation

Abstract: Background Reflective practice is a key skill for healthcare professionals. E-learning programmes have the potential to develop reflective practice in remote settings and low- and middle-income countries (LMICs), where access to in-person reflective groups may be reduced. ‘Aqoon’ is a global mental health peer-to-peer e-learning programme between Somaliland and UK medical students. We aimed to explore participants’ experiences of participating in the Aqoon programme, including their experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Certain elements were both enablers and barriers, specifically funding, the need for protected and convenient course timing, and technological support needed for VGHEA implementation. The double mention of these factors highlights their critical importance to the success of VGHEAs; indeed, those articles that mentioned funding, [47][48][49][50][51][52] timing, 40,[53][54][55] and strong technology 40,49,53,54,[56][57][58][59][60][61][62] as facilitators of VGHEAs offer key insights into how to overcome barriers that may prevent successful VGHEA implementation. More research in this area will be important to guide the planning and development of VGHEAs, particularly between HIC/LMIC partners who will have different needs and capacities.…”
Section: Vghea = Virtual Global Health Education Activitymentioning
confidence: 99%
“…Certain elements were both enablers and barriers, specifically funding, the need for protected and convenient course timing, and technological support needed for VGHEA implementation. The double mention of these factors highlights their critical importance to the success of VGHEAs; indeed, those articles that mentioned funding, [47][48][49][50][51][52] timing, 40,[53][54][55] and strong technology 40,49,53,54,[56][57][58][59][60][61][62] as facilitators of VGHEAs offer key insights into how to overcome barriers that may prevent successful VGHEA implementation. More research in this area will be important to guide the planning and development of VGHEAs, particularly between HIC/LMIC partners who will have different needs and capacities.…”
Section: Vghea = Virtual Global Health Education Activitymentioning
confidence: 99%
“…Enforcing of daily reflections caused users to reflect on experiences that were insignificant [ 119 , 235 , 236 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that RW does not cater to the different learning styles [ 220 , 232 ], cultures [ 190 ], roles, values, processes and expectations of RW [ 114 , 129 , 135 , 138 , 142 , 209 , 227 , 234 ], and physicians' differing levels of self-awareness [ 29 , 79 , 119 , 176 , 188 , 226 , 231 , 236 ], motivations [ 29 , 119 , 136 , 138 , 157 , 161 , 167 169 , 176 , 181 , 193 , 196 , 226 , 232 , 233 ] and willingness to engage in RW [ 37 , 114 , 136 , 149 , 160 , 183 ]. RW is also limited by poorly prepared physicians and misaligned expectations whilst a lack of privacy and a safe setting may precipitate physician anxiety at having their private thoughts shared [ 129 , 149 , 209 , 231 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies used quasi-experimental designs ( 14), followed by descriptive designs (9), randomized controlled trials (3), and mixed methods (2). Others included a case study (Peterson et al, 2016) and a qualitative study (Prosser et al, 2021).…”
Section: Study Designsmentioning
confidence: 99%
“…However, these were time-consuming and costly. Alternatives include written reflections which are less time-consuming to administer and provide a similar level of information (Prosser et al, 2021). Suggestions to improve written reflections were around incentives for completion (e.g., grade incentives), using validated methodologies (e.g., SWOT), providing real-time feedback (i.e., immediate versus delayed feedback), and capturing long-term data (e.g., post-course follow-up).…”
Section: Focus Groups and Written Reflectionsmentioning
confidence: 99%